Ontogeny of the Anterior Clinoid Process: A CT ‐Based Lifespan Analysis of Growth, Pneumatization, and Parasellar Variations - Wilairat Kankuan Kaewborisutsakul; Anukoon Kaewborisutsakul; Chin Taweesomboonyat; Nuttha Sanghan; Sarayut Lucien Geater (Clinical Anatomy, 2026)
ABSTRACT The anterior clinoid process (ACP) is a surgically critical skull base structure, the continuous postnatal ontogeny of which remains poorly characterized. We mapped the chronological trajectory of ACP morphometric maturation, pneumatization, and parasellar variation across the human lifespan. We evaluated 300 cranial CT scans (600 ACP sides) across stratified age cohorts from birth to adulthood. Six morphometric dimensions were measured bilaterally and modeled using nonlinear growth curves (restricted cubic splines and multivariable fractional polynomials; 1000 bootstrap replications) to derive the radiographic maturation age at the 95% adult plateau. ACP pneumatization was classified using our validated eight‐subtype, route‐based system. Middle clinoid process (MCP) and interclinoid calcification (ICC) were independently documented for each side across all age groups. ACP maturation followed a three‐stage hierarchical developmental sequence. The base stabilized earliest, with base width maturing in infancy (1.0 year), followed by base and midpoint thickness (2.1–2.2 years). Lateral expansion and anterior spatial projection matured pre‐pubertally (10.0–11.0 years). Sagittal elongation (ACP length), the last dimension to mature, showed sexual dimorphism, plateauing at 13.0 years in females and 16.0 years in males. Pneumatization emerged sequentially: optic strut aeration (Type 1) appeared at 7 years, true ACP body pneumatization (Types 2a/2b) appeared at 12 years, and multiroute pneumatization was restricted to adults. The MCP is present in early childhood, consistent with a congenital origin, whereas ICC progressively emerges after the first decade. The ACP undergoes a hierarchical sequence of structural development, regulated by distinct directional growth vectors. This three‐stage maturation timeline and late‐onset ACP pneumatization underpin the substantially lower risk of inadvertent sinus entry during anterior clinoidectomy in pediatric patients.